THE USE OF INNOVATIVE TEACHING TASKS IN THE PROVISION OF ENVIRONMENTAL EDUCATION TO ELEMENTARY STUDENTS - Ismatillaeva , Yodgora (Educational Research in Universal Sciences, 2023)
This article covers current issues of the development of the educational system, ways of providing environmental education to primary school students, mechanisms for using innovative educational tasks in the provision of environmental education.